Sybil, or, the two nations - Disraeli, Benjamin, 1804-1881 (Floating Press, 2010)
Sybil was written by Benjamin Disraeli, future Prime Minister of Great Britain. He was greatly concerned with the poverty of the working classes, and this novel, with its in-depth exploration of those conditions, expressed and circulated his ideas.